A novel prediction model to evaluate the probability of CD4+/CD8+ cell ratio restoration in HIV-infected individuals. (1st May 2022) - Li, Bei; Zhang, Leidan; Liu, Ying; Xiao, Jing; Li, Cuilin; Fan, Lina; Duan, Yujiao; Xiao, Jiang; Hao, Yu; Han, Junyan; Kong, Yaxian; Zhao, Hongxin
Abstract : Background: Our study aimed to develop a clinical prediction model to evaluate the possibility of CD4 + /CD8 + ratio restoration in HIV-positive individuals. Methods: About 1980, HIV/AIDS patients initiated with antiretroviral treatment from 1 January 2013, to 30 December 2016, at Beijing Ditan Hospital and achieved persistent virological suppression during the 4 years follow-up were included in this study. Multivariate Cox proportional regression analysis was used to identify the independent risk factors and establish a predictive model. The model's performance was assessed using the area under the receiver operating characteristic and calibration plots. Results: Overall, after 4 years of treatment, a total of 455 individuals (22.98%) restored their CD4 + /CD8 + ratio (≥1). The area under the receiver operating characteristic was 0.782 and 0.743 in the deriving and validation cohort, respectively. The ultimate model included five indexes: age at AIDS diagnosis, albumin, and syphilis status, and baseline CD4 + and CD8 + values. A nomogram further visualized the model, and the calibration plots indicated high agreement of predicted and observed outcomes. Conclusion: Our prediction model might be practical and easily applied to recognize HIV/AIDS individuals most likely to benefit from modern antiretroviral therapy.